Assessment of Knowledge, Practice, and Perception about Social Media in Dentistry among Dental Students at Chengalpattu District: A Cross-sectional Study - G Keerthana; K Indrapriyadharshini; Vishnu Prasad Subraman; S Keerthana; Mahesh Jagadeson; Karthikayan Ravi; M. P. Revanth (Wolters Kluwer Medknow Publications, 2024)
Background: Social media has brought incredible changes in recent times due to expanding online technological aspects which help health-care professionals to utilize them to improve patient health outcomes. It acts as an effective mode of communication for dentists to interact with patients around the globe which builds up good doctor-patient relationships. Furthermore, social media has become an abundant source of health-care patient information and acts as an excellent resource to promote health education among people. Aim: This study aims to evaluate the knowledge, practice, and perception of social media in dentistry among dental students and to identify the common social media platform used by dental students to share their online dental-related posts and further evaluate their perception toward usage of social media as a tool for dental practice to share information about dental-related diseases. Materials and Methods: This cross-sectional study was conducted as an online survey using self-constructed questionnaires among the undergraduate and postgraduate students at Karapaga Vinayaga Institute of Dental Sciences over 6 months, from July 15, 2023 to January 15, 2024. Participants' consent was sought and ethical approval was received from the Ethical Review Committee. Results: About 71.6% of the postgraduates, 68.8% of interns, and 49.45% of final-year undergraduates responded that dentistry should have an online presence with a statistically significant value of P = 0.007. The majority of about 75.3% of the postgraduates accepted that social media is effective in dental practice. This states that postgraduates contribute to higher knowledge and have adequate practice in using social media in dentistry which was statistically significant. Conclusion: The present study identified that postgraduates contribute more in the count for sharing sufficient knowledge and also practice in using social media in dentistry. This study explains that it is the responsibility of dentists to educate patients more about utilizing social media as a key to gaining knowledge about dental diseases and treatment procedures. Clinical Significance: This study aims to identify the need for dentists to know more about the utilization of social media in dentistry to promote dental health education and to help the general population acquire knowledge about various dental diseases and their treatment procedures.